PERAN KEPALA DESA DAN PARTISIPASI MASYARAKAT UNTUK MEWUJUDKAN TATA KELOLA KEUANGAN YANG TRANSPARAN DAN AKUNTABEL DI DESA BIREM PUNTONG,KOTA LANGSA - Muhammad Salman; Siti Rohani (Program Studi Akuntansi Fakultas Ekonomi Universitas Samudra, 2019)
This study aims to determine the influence of the role of the village head and community participation in transparent and accountable village financial management in BiremPuntong Village. This research was conducted in BiremPuntong Village, LangsaBaro District. The population in this study were all family heads in BiremPuntong Village as many as 732, and samples taken as many as 88 respondents. This study was tested using multiple linear regression. Based on the results of the study it was concluded that the role of the village head and community participation, both partially and simultaneously, influenced village financial governance. transparent and accountable in BiremPuntong Village, Langsa Baro District